Analysis of the benefits of using e-modules as distance learning media: can it help students improve cognitive and affective aspects of students? - Holisoh, Ade; Nurhalimah, Nurhalimah; Hamda, Nasmal (Gema Wiralodra, 2023)
One learning tool with many advantages is interactive e-learning. These e-modules include text, graphics, animation, and videos, making it easier for students to understand lessons, especially when studying remotely. This study uses a literature review methodology to collect information from various sources, including books, articles from online journals, well-known websites, and statistical data from the internet. The information is then investigated and checked through three stages, including descriptive analysis, content analysis, and critical analysis. Based on research findings conducted through library research, interactive e-modules can increase student motivation, scientific literacy skills, learning outcomes, independence, and critical thinking skills. Based on the research results, this e-module can be used by teachers in distance learning as a learning media based on research findings. Interactive e-modules can increase learning motivation, scientific literacy, learning outcomes, independence, and students critical thinking skills.